(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
The purpose of this study is to identify important destination attributes of Kandy city and examine how and to what extent those attributes impact on international tourists’ decision on choosing their destination. A proposed model was formulated and it postulates that international tourists’ perception of Kandy City important attributes that impacts on their decision making in three ways: (1) directly; (2) it influences on the overall image of Kandy city, and in turn, influences their decision; (3) it also impacts on the international tourists’ overall satisfaction with their trip to Kandy city, and in turn, influences their own or their peripheral people future decision on destination selection. Destination attributes were identified based on a triangulation approach prior to the research. A structured questionnaire was used to collect the data. One hundred and sixty (160) international tourists (millennial) were selected as the sample. In addition, 15 millennial tourists were interviewed to prove the findings of survey further. The valid data collected was computed by means of the SPSS to gain basic frequency statistics. The results also showed that, the Kandy city attributes revealed different importance levels in influencing tourists’ destination decision making, formation of Kandy city overall image, and the tourists’ satisfaction.